2017
DOI: 10.1371/journal.pone.0182718
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between self-assessed hearing status and measured audiometric evaluation

Abstract: ObjectiveThe purpose of this study was to examine the difference between self-reported hearing status and hearing impairment assessed using conventional audiometry. The associated factors were examined when a concordance between self-reported hearing and audiometric measures was lacking.MethodsIn total, 19,642 individuals ≥20 years of age who participated in the Korea National Health and Nutrition Examination Surveys conducted from 2009 through 2012 were enrolled. Pure-tone hearing threshold audiometry (PTA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 39 publications
(55 reference statements)
13
55
1
Order By: Relevance
“…The ability of the question to identify hearing loss increases substantially when other factors are taken into account, with age being the most important one. Our results are in line with the increasing support in literature for using a single question as an estimator for hearing loss in absence of pure tone audiometry [14,15,[23][24][25][26][27][28]. There is a growing general interest in applying this concept to large population-based studies, for which time or other resources to perform audiometry are not available [29,30].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The ability of the question to identify hearing loss increases substantially when other factors are taken into account, with age being the most important one. Our results are in line with the increasing support in literature for using a single question as an estimator for hearing loss in absence of pure tone audiometry [14,15,[23][24][25][26][27][28]. There is a growing general interest in applying this concept to large population-based studies, for which time or other resources to perform audiometry are not available [29,30].…”
Section: Discussionsupporting
confidence: 88%
“…Self-reporting always comes with the risk of misclassification bias, resulting in under-and overestimation. Age, sex and educational level, amongst other factors, are shown to be associated with identification of self-reported hearing loss [24,25,33] and objective hearing loss and are easily assessable in any situation [1,14,15,24,33,34]. We found age, sex and educational level to increase the ability of the question to identify hearing loss, with age being the most important factor by far.…”
Section: Discussionmentioning
confidence: 69%
“…Because middle-aged adults have more opportunities to participate in social communication and often have jobs, they could be more affected by impaired verbal communication. In contrast, older adults tend to be more accommodating and often do not perceive their hearing impairment 21 , 22 . Thus, older adults might be more protected than middle-aged adults from the social isolation and emotional problems due to hearing impairment.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, Kamil et al (2015) found that older women and Hispanics with hearing loss were less likely to self-report hearing loss compared to other demographic groups with hearing loss. Choi et al (2019) , Kim et al (2017) , and Wang et al (2019) analyzed self-report data from Korean and Chinese population samples and found that women were more likely to overestimate their hearing loss as compared to men who were more likely to underestimate their hearing loss. Although the literature may not be conclusive on the effect of gender and culture on self-report of hearing loss, we still acknowledge this limitation of our study sample.…”
Section: Discussionmentioning
confidence: 99%